(3GdGUdGM GdGbJUGOj h SjGSI GdJTZjd (B:s (3GdJLQHI GdLRGFQjI (B/s - (3Hf TgQI, eOfjs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2008)
(3adSaI HQfGeL GdEUdGM GdGbJUGOj GdPj jDGRQhg UfOhb GdfbO GdOhdj (B-(3GdKfGFjI GdYGdejI hSjGSI GdEUdGM GdGbJUGOj (B-(3feGPL GdEUdGM GdGbJUGOj GdQFjSjI GdebJQMI ef NHQGA UfOhb GdfbO GdOhdj(B-(3GdLRGFQ hUfOhb GdfbO GdOhdj(B-(3JMdjd JWhQ GdJTZjd aj GdLRGFQ(B(1966-1999) -(3BKGQ SjGSI GdEUdGM Ydi eSJhi GdJTZjd hGdHWGdI (B-(3CSHGH eTcdI GdHWGdI aj GdLRGFQ hJbjje SjGSGJ YdGLgG (B-(3GdELQGAGJ GdeQGabI dHQfGeL GdEUdGM GdGbJUGOj ddJNaja ef BKGQgs
((3EbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdEUdGM GdEbJUGOjs; (3JTZjds; (3SjGSI GdJTZjds; (3UfOhb GdfbO GdOhdjs